Cassava and sweet potato. Suitability of popular Caribbean varieties for value added product development - Titus, Pathleen (IICA, 2017)
The information presented herein is the outcome of a project, “Enhancing the Value Added Processing of Roots and Tubers in the Caribbean through the Transfer of Improved Technologies” funded by the Inter-American Institute for Cooperation on Agriculture Competitive Fund for Technical Cooperation (FonTC). The overall goal of the project was to improve the capacity of Caribbean countries to attain the Region’s food and nutrition security strategy as it pertains to staples. This project was executed in four target countries (Barbados, Dominica, St Kitts and Nevis and Trinidad and Tobago) where cassava and sweet potato production have traditionally been important to livelihoods of many small farmers and processors. The information is intended for processors as well as producers who are supplying raw materials to processors.